Dança e educação: visão de jovens bailarinos da edisca - Mangualde, Isadora Nogueira (2017)
This work originated from the fundamental idea that dance can provide several benefits to the human being, from biological and social aspects to cultural and educational dimensions. In this sense, the starting point was the interest in analyzing the interaction of dance with education in the integral development of people, especially children and young people, participants in the formative actions in this specific area of art. The central question of the research was then: what is the relation between dance and education in the vision of young dancers? With this, the objective of the study was to understand this relation, based on the themes of Art, Dance, and Education, based on authors such as Duarte Júnior, Coli, Garaudy, Freire, Vygotsky, and others. Edisca, the locus of research, offers educational activities focused on dance, for children and adolescents in conditions of social vulnerability. A qualitative research was developed along the line of case study and, in it, parts of the routine were observed and interviews were carried out with the psychologist, who is one of the coordinators, to contextualize the study and approach with the institution, and also with young dancers, in order to identify their views about the relation. With the studies and data collected, the work showed that the young people consider that Edisca provides enriching experiences, internally and externally to its institutional space. Dance has a broad meaning in the life of the dancers, who give it so great importance that they consider it as part of them, as a means of expression, without the need to use words. About the school profile of these interviewees, half of them are from a private college and the other half study in public schools. This led to different feelings on the part of them: the scholars emphasized the school as an important space for human relations, and, the other students pointed out, mainly, aspects to improve, such as poor physical structure and lack of some teachers in these public schools. From the perspective of young people, the richness of the dance/education interaction in integral development was verified. It is possible to relate aspects involved and benefits provided by dance practice: physical – development of strength and agility; psychological – overcoming shyness and personal well-being; social – group work and participation in events; intellectual – attention and determination; among others. With this, it is believed that the dance/education relation must be experienced by all, as it provides bodily awareness, self-knowledge and many fundamental experiences for the formation of more creative and active people in society.